THE IMPACT OF DIGITAL TECHNOLOGIES ON THE DEVELOPMENT OF ESP STUDENTS’ WRITING COMPETENCE - Jabborova, Dilafruz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In the context of English for Specific Purposes (ESP), developing writing competence is crucial for success in global communication, especially as digital technologies increasingly shape educational practices. This article explores the influence of digital tools on the writing development of ESP students, highlighting both the advantages and potential drawbacks. Through a mixed-method study involving 100 ESP students, the research analyzes how digital platforms and applications enhance technical language, sentence structure, and professional writing formats. While digital tools foster improved writing abilities and engagement, the study also raises concerns about the over-reliance on technology and its impact on critical self-editing skills. The findings suggest that while digital technologies offer significant benefits, educators must balance their use with the reinforcement of core writing competencies.